Kajian Bentuk, Fungsi, dan Makna Pakaian Adat Depati Ninik Mamak Desa Seleman Kecamatan Danau Kerinci - Nadia, Nadia; Pebriyeni, Eliya (TSAQOFAH, 2025)
This study aims to identify and describe the form, function, and meaning of traditional clothing worn by Depati and Ninik Mamak during customary ceremonies in Seleman Village, Danau Kerinci District. The research employed a qualitative method with a descriptive approach, using interviews with local Depati and Ninik Mamak as key informants. The findings show that the traditional attire consists of several main components, including sungkuk, baju gedeang, suwan gedeang, kain tahhap, cinggang/cawek, kehaih, tungkat, and shoes. Each element carries both symbolic and practical functions, serving as markers of social status and cultural identity within the Kerinci customary structure. The clothing not only enhances appearance during ceremonial events but also represents local wisdom values such as honor, authority, responsibility, and exemplary conduct. The philosophical meanings embedded in the attire reflect community norms and worldviews rooted in customary law. These findings indicate that traditional clothing serves not only as a form of material cultural heritage but also as a medium for transmitting social values and the collective identity of the Kerinci indigenous community.